Project-Based Learning in Analytical Chemistry 1 Course With A Blended Learning System and Study Graduate Learning Outcomes - Rosinda Tinenti, Yanti; Tangi, Hironimus; H. B. Hayon, Vinsensia; Wariani, Theresia (Jurnal PAJAR (Pendidikan dan Pengajaran), 2024)
This study aims to examine the implementation of the PBP model stages in the lecture process and student graduate learning outcomes (CPL) in the analytical chemistry course in the 1st semester of the academic year 2020/2021 which applies the PBP model with a blended learning system. This type of research is descriptive quantitative. In carrying out this research, it is preceded by planning the lecture process using a project-based learning model (PBP), applying it in the lecture process with a blended learning system, then conducting a process assessment, and seeing the achievement of CPL in the analytical chemistry course I in the form of quantitative values, and further described. The qualitative descriptive type is a type of research to see the implementation of the PBP model steps with a blended learning system and the achievement of CPL. Data was obtained by using observation techniques in the form of narratives and then examined for their suitability with relevant theories and studies related to the implementation of the PBP model steps. The results of this study are the PBP model with a blended learning system in the analytical chemistry course I was carried out well according to the planning, design, implementation, and reporting stages, CPL KU and KK were declared achieved based on the assessment of sub CPMK 6, 7, 8, 9 with the average percentage of achievement is 100, 78, 80, 84, 77 and in general the percentage of achievement for CPl KU 5 and KK 4 is 100% and 79.75%